SHANK2 is a frequently amplified oncogene with evolutionarily conserved roles in regulating Hippo signaling. Issue 3 (13th July 2020) - Xu, Liang; Li, Peixue; Hao, Xue; Lu, Yi; Liu, Mingxian; Song, Wenqian; Shan, Lin; Yu, Jiao; Ding, Hongyu; Chen, Shishuang; Yang, Ailing; Zeng, Yi Arial; et al.
Abstract: Dysfunction of the Hippo pathway enables cells to evade contact inhibition and provides advantages for cancerous overgrowth. However, for a significant portion of human cancer, how Hippo signaling is perturbed remains unknown. To answer this question, we performed a genome-wide screening for genes that affect the Hippo pathway in Drosophila and cross-referenced the hit genes with human cancer genome. In our screen, Prosap was identified as a novel regulator of the Hippo pathway that potently affects tissue growth. Interestingly, a mammalian homolog of Prosap, SHANK2, is the most frequently amplified gene on 11q13, a major tumor amplicon in human cancer. Gene amplification profile in this 11q13 amplicon clearly indicates selective pressure for SHANK2 amplification. More importantly, across the human cancer genome, SHANK2 is the most frequently amplified gene that is not located within the Myc amplicon. Further studies in multiple human cell lines confirmed that SHANK2 overexpression causes deregulation of Hippo signaling through competitive binding for a LATS1 activator, and as a potential oncogene, SHANK2 promotes cellular transformation and tumor formation in vivo . In cancer cell lines with deregulated Hippo pathway, depletion of SHANK2 restores Hippo signaling and ceases cellular proliferation. Taken together, these results suggest that SHANK2 is an evolutionarily conserved Hippo pathway regulator, commonly amplified in human cancer and potently promotes cancer. Our study for the first time illustrated oncogenic function of SHANK2, one of the most frequently amplified gene in human cancer. Furthermore, given that in normal adult tissues, SHANK2's expression is largely restricted to the nervous system, SHANK2 may represent an interesting target for anticancer therapy.